Mapping and assessment of the state of wetland ecosystems: a Mediterranean perspective (2022)
Authors: Marco Trombetti, Dania Abdul Malak, Antonio Sanchez (ETC-UMA); Anis Guelmami (Mediterranean Wetlands Observatory, Tour du Valat); Nieves Garcia (environmental consultant); Eleni Fitoka (Greek Biotope / Wetland Centre - EKBY)